Mensurando o sentimento de incerteza da política econômica: uma análise a partir da comunicação do Banco Central do Brasil - Silva, Pierre Hítalo Nascimento (2020)
This dissertation has two main purposes. The first is to create an index capable of measuring the degree of uncertainty of economic policy in Brazil. This index will be built from the estimation of the textual sentiment contained in the minutes of meetings of the Monetary Policy Committee (COPOM) in the period 2000-2018. The second purpose is to analyze the impacts of the Central Bank’s communication under a set of macroeconomic variables in Brazil based on the textit Factor-Augmented Vector Autoregressive (FAVAR) model. It is concluded that the communication of the Central Bank has the capacity to affect macroeconomic variables and influence the posture of economic agents, in addition to being interconnected with the political context.